Circulating S100B and Adiponectin in Children Who Underwent Open Heart Surgery and Cardiopulmonary Bypass. (31st August 2015) - Varrica, Alessandro; Satriano, Angela; Frigiola, Alessandro; Giamberti, Alessandro; Tettamanti, Guido; Anastasia, Luigi; Conforti, Erika; Gavilanes, Antonio D. W.; Zimmermann, Luc J.; Vles, Hans J. S.; Li Volti, Giovanni; Gazzolo, Diego
Abstract : Background . S100B protein, previously proposed as a consolidated marker of brain damage in congenital heart disease (CHD) newborns who underwent cardiac surgery and cardiopulmonary bypass (CPB), has been progressively abandoned due to S100B CNS extra-source such as adipose tissue. The present study investigated CHD newborns, if adipose tissue contributes significantly to S100B serum levels. Methods . We conducted a prospective study in 26 CHD infants, without preexisting neurological disorders, who underwent cardiac surgery and CPB in whom blood samples for S100B and adiponectin (ADN) measurement were drawn at five perioperative time-points. Results . S100B showed a significant increase from hospital admission up to 24 h after procedure reaching its maximum peak ( P < 0.01 ) during CPB and at the end of the surgical procedure. Moreover, ADN showed a flat pattern and no significant differences ( P > 0.05 ) have been found all along perioperative monitoring. ADN/S100B ratio pattern was identical to S100B alone with the higher peak at the end of CPB and remained higher up to 24 h from surgery. Conclusions . The present study provides evidence that, in CHD infants, S100B protein is not affected by an extra-source adipose tissue release as suggested by no changes in circulating ADN concentrations.